1976
DOI: 10.1073/pnas.73.2.381
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of a serum factor that causes necrosis of tumors.

Abstract: Tumor necrosis can be induced in transplanted mouse methylcholanthrene-induced sarcoma by a tumor necrosis factor in the serum of mice infected with bacillus Calmette-Guerin and given bacterial endotoxin. Sera from normal mice, endotoxin-treated mice, and mice infected with bacillus Calmette-Guerin do not contain this factor. A 20-to 30-fold purification of the serum factor has been achieved by (NH4)2SO4 fractionation, Sephadex Fig. 1. No significant difference was found between normal and endotoxin-treated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
2
1

Year Published

1977
1977
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(61 citation statements)
references
References 16 publications
1
57
2
1
Order By: Relevance
“…The background activity of NMS can partly be ascribed to the presence of minor amounts of TNF (Shah, Green & Moore, 1978;Green, Chiasson & Shah, 1979) and partly to another factor shown to inhibit DNA synthesis by mouse lymphocytes (Nelson & Shneider, 1974;Smith & HammarstrOm, 1979). This factor shares some physicochemical characteristics with TNF such as its nondialysable glycoprotein nature, its heat-stability (30 min, 56°C) and its electrophoretic mobility as an a-globulin (Nelson & Shneider, 1974;Green, Dobrjansky, Carswell, Kassel, Old, Fiore & Schwartz, 1976). TNF, however, has another elution pattern on Sephadex G20 o (Green et al, 1976) and unlike the other inhibitory factor (Nelson, 1972), cannot be demonstrated nor induced in serum of nude mice (Hoffmann, Oettgen, Old, Mittler & Hammerling, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The background activity of NMS can partly be ascribed to the presence of minor amounts of TNF (Shah, Green & Moore, 1978;Green, Chiasson & Shah, 1979) and partly to another factor shown to inhibit DNA synthesis by mouse lymphocytes (Nelson & Shneider, 1974;Smith & HammarstrOm, 1979). This factor shares some physicochemical characteristics with TNF such as its nondialysable glycoprotein nature, its heat-stability (30 min, 56°C) and its electrophoretic mobility as an a-globulin (Nelson & Shneider, 1974;Green, Dobrjansky, Carswell, Kassel, Old, Fiore & Schwartz, 1976). TNF, however, has another elution pattern on Sephadex G20 o (Green et al, 1976) and unlike the other inhibitory factor (Nelson, 1972), cannot be demonstrated nor induced in serum of nude mice (Hoffmann, Oettgen, Old, Mittler & Hammerling, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…This factor shares some physicochemical characteristics with TNF such as its nondialysable glycoprotein nature, its heat-stability (30 min, 56°C) and its electrophoretic mobility as an a-globulin (Nelson & Shneider, 1974;Green, Dobrjansky, Carswell, Kassel, Old, Fiore & Schwartz, 1976). TNF, however, has another elution pattern on Sephadex G20 o (Green et al, 1976) and unlike the other inhibitory factor (Nelson, 1972), cannot be demonstrated nor induced in serum of nude mice (Hoffmann, Oettgen, Old, Mittler & Hammerling, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have reported that injection of LPS to bacille Calmette-Gu~rin-infected mice causes the release of a factor into the serum which also substitutes for helper T cells (4). Because serum produced in this fashion causes acute necrosis of subcutaneous tumor grafts, it is termed tumor necrosis serum (TNS) (5), and its tumor-necrotizing component is referred to as tumor necrosis factor (TNF) (6). TNF is contained in a glycoprotein fraction (mol wt 150,000) which migrates with the a2 macroglobulins (6).…”
mentioning
confidence: 99%
“…Because serum produced in this fashion causes acute necrosis of subcutaneous tumor grafts, it is termed tumor necrosis serum (TNS) (5), and its tumor-necrotizing component is referred to as tumor necrosis factor (TNF) (6). TNF is contained in a glycoprotein fraction (mol wt 150,000) which migrates with the a2 macroglobulins (6). Although the factor that substitutes for T cells is also found in that fraction, it is not known if the two are identical.…”
mentioning
confidence: 99%
“…Caused hemorrhagic necrosis of transplanted tumors. A factor responsible for the antitumor activity of the serum has been designated tumor necrosis factor (TNF ), which is believed to be a lysosomal enzyme released from activated macrophages (Green et al 1976 ;Matthews and Watkins 1978).…”
Section: Discussionmentioning
confidence: 99%